The Role of Adversity Intelligence in Moderating the Influence of Individual Motivation on Entrepreneurial Success - Yuni Siswanti; Joko Susanto; Emmy Nurhariati; Sudaryati Sudaryati (Journal of International Conference Proceedings, 2021)
This study aims to test: 1) the influence of individual motivation on entrepreneurial success and 2) the role of adversity intelligence in moderating the influence of individual motivation on entrepreneurship success. This research was conducted with a survey. The population taken is vocational school alumni in the Special Region of Yogyakarta (Sleman Regency, Madya City, Bantul, Kulon Progo and Gunung Kidul) who experienced job cuts due to the covid-19 pandemic. Sampling by convenience sampling and data retrieval by spreading questionnaires (google form). Sampling by convenience sampling and data retrieval by spreading questionnaires (google form). The number of respondents who filled out and returned the questionnaire were 112 peoples—test instruments with confirmatory factor analysis and reliability by looking at Cronbach Alpha. The hypothesis test uses a simple regression (H1) and a tiered regression test (H2). The results showed that H1 and H2 were supported. There are some limitations in this research that require further investigation. This research has theoretical and managerial implications for business people. The discussion results showed that further research was needed discussing.